Supporting the role and enabling the potential of community health workers in Bangladesh’s rural maternal and newborn health programs: A qualitative study - Adams, Alayne M; Vuckovic, Myriam; Graul, Emily; Rashid, Sabina F; Sarker, Malabika (Journal of Global Health Reports, 2022)
This article was published in Journal of Global Health Reports [ This is an open-access article distributed under the terms of the Creative Commons Attribution 4.0 International License (CCBY-4.0).] and the definite version is available at: https://doi.org/10.29392/001c.12682 The Journal's website is at: https://www.joghr.org/article/12682-supporting-the-role-and-enabling-the-potential-of-community-health-workers-in-bangladesh-s-rural-maternal-and-newborn-health-programs-a-qualitative-study